[PP.13.05] BIRTH WEIGHT AND ITS ASSOCIATIONS WITH BLOOD PRESSURE AND BODY MASS INDEX OF STUDENTS AGED 10 TO 15 YEARS. RIO DE JANEIRO STUDY II. (September 2017) - Brandao, A.; Fonseca, F.; Magalhaes, M.; Campana, E.; Spineti, P.; Pozzan, R.; Silva, E.; Bouzas, J.; Bouzas, G.; Harboe, B.; Guimaraes, L.; Almeida, A.; et al.
Abstract : Objective: To analyze birth weight (BW) and its association with blood pressure (BP) and body mass index (BMI) of 10 to 15 year old students of public schools in Brazil Design and method: Cross-sectional study. A total of 1, 723 students were evaluated in the school environment: 743 (43.1%) males (M) and 980 (56.9%) females (F). The distribution of the population by age and gender was: 10 yo (n = 108, 49 M / 59F), 11 yo (n = 242, 106 M 136F), 12 yo (n = 368, 397, 161 M / 236F), 14 yo (n = 346, 153 M / 193F), 15 yo (n = 262, 105 M / 157F). BP was measured three times by oscillometric method with OMROM HEM-1720 automatic monitor and the BMI calculated from the weight and height. BW was obtained through information provided by the parents or guardian. The students were divided into tertiles referring to birth weight: first tertile (T1) <3000 g; Second tertile (T2) > = 3000 g and <3450 g; and third tertile (T3) > = 3450 g. Results: Systolic BP means were not statistically different comparing BW tertiles (T1: 108.84 ± 11.93 mmHg, T2: 108.23 ± 11.06 mmHg, T3: 107.78 ± 10.22 mmHg) (p = 0.315); Diastolic BP means did not show statistically significant differences between the tertiles of BW (T1: 63.37 ± 10.77 mmHg, T2: 62.67 ± 9.04 mmHg, T3: 62.84 ± 8.83 mmHg) (p = 0.503); BMI means were statistically different between the groups, the mean of T3 being greater than T1 (p = 0.008) (T1: 20.49 ± 4.28 kg / m 2, T2: 21.13 ± 4.58 kg / m 2 ; T3: 21.31 ± 4.24 kg / m 2). Comparison of students with BW < = 2500 g (low BW, n = 184) and BW > 2500 g (normal BW, n = 1292) showed lower BMI mean (p = 0.043) and higher BP mean (not significant) in the low BW group. Conclusions: Students aged 10–15 years with lower BW had higher BP, but with no statistical significance. However, greater birth weight was significantly associated with higher BMI in adolescence.